2015
DOI: 10.1111/cns.12386
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and Challenges: Stem Cell‐Based Therapy for the Treatment of Ischemic Stroke

Abstract: Stem cell-based therapy for ischemic stroke has been widely explored in animal models and provides strong evidence of benefits. In this review, we summarize the types of stem cells, various delivery routes, and tracking tools for stem cell therapy of ischemic stroke. MSCs, EPCs, and NSCs are the most explored cell types for ischemic stroke treatment. Although the mechanisms of stem cell-based therapies are not fully understood, the most possible functions of the transplanted cells are releasing growth factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 182 publications
(166 reference statements)
1
54
0
4
Order By: Relevance
“…Recently, basic and clinical studies have found that the transplantation of bone marrow-derived mesenchymal stem cells (BMSCs) is a promising therapeutic strategy for brain tissue repair following brain ischemia. 1) However, the therapeutic efficacy of this procedure is greatly limited by the poor survival of transplanted BMSCs in the infarcted brain tissue. After transplantation, BMSCs face hostile microenvironments in the ischemic brain, including oxidative stress, hypoxia and inflammatory reactions, which promote cell apoptosis.…”
mentioning
confidence: 99%
“…Recently, basic and clinical studies have found that the transplantation of bone marrow-derived mesenchymal stem cells (BMSCs) is a promising therapeutic strategy for brain tissue repair following brain ischemia. 1) However, the therapeutic efficacy of this procedure is greatly limited by the poor survival of transplanted BMSCs in the infarcted brain tissue. After transplantation, BMSCs face hostile microenvironments in the ischemic brain, including oxidative stress, hypoxia and inflammatory reactions, which promote cell apoptosis.…”
mentioning
confidence: 99%
“…Both BM‐EPCs and BM‐MSCs express SP receptor NK‐1R, and SP is known to mobilize BM‐MSCs from the bone marrow into the blood and aid in their recruitment to the injured tissue . We explored whether SP treatment can affect the tube‐forming capacity of the MSCs and/or EPCs.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, early resolution of the blood clots within 6 hours after a stroke is the only clinically approved treatment, and a very small portion of patients qualify for such treatment . Despite decades of research on numerous animals and clinical trials, the outcomes of stem cell therapies have not reached clinical expectations . Severe tissue‐destructive inflammatory microenvironments and a very low rate of homing and survival of the transplanted cells have been suggested as reasons contributing to their therapeutic inefficiency .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that high quantities of intranasally delivered stem cells can enter the CNS, concentrate specifically at disease foci, and exert effects for several months post-infusion (Li et al, 2015). The safeness and efficiency of the intranasal delivery has been investigated in animal models of various neurological diseases (Tang et al, 2015). However, intranasal delivery has some disadvantages, such as active mucociliary clearance, enzymatic degradation, and low pH of the nasal epithelium, low permeability without absorption enhancers, as well as individual variability, which may cause low CNS delivery efficiencies and necessitate the delivery of high doses (Lochhead and Thorne, 2012).…”
Section: Stem Cells At the Forefront Of Basic Researchmentioning
confidence: 99%